A RE-ASSESSMENT OF WOMEN MARGINALIZATION IN GOVERNANCE IN NIGERIA 1999-2011 (2014)
The relatively low level of women political representation between 1999 (7.5%) and 2011 (14.0%), at the federal level, is an indication that women are marginalised in governance in Nigeria. Previous studies on gender relations and governance in Nigeria largely focused on the marginalisation of women by men with negligible attention on the role of women in this gender-based political imbalance. This study, therefore, investigated the role of women in women’s marginalisation in governance between 1999-2011 democratic dispensations. The study adopted a survey design and used radical feminism framework as a guide. A state was randomly selected from the six geopolitical zones. The Federal Capital Territory (Abuja), (Kaduna, Makurdi,Yola, Ibadan) and two rural areas (Ubulu-Uku and Obiohia) were purposively selected. A total of 1196 participants comprising male 793 and female 403 were selected using accidental sampling technique, within the required class of Nigerian adults (20-70yrs). Semi structured questionnaire was used to collect data on existing frameworks, their effectiveness, the need for paradigm shift, the role of government, culture, economy and women in women marginalization. Also, six In-depth Interviews and six Focus Group Discussions (FGD) of 6-8 participants were conducted in the six states with selected leaders of non-governmental organisations in the area of gender advocacy. Quantitative data were analysed using descriptive statistics and Chi-square test at p < 0.05 while qualitative data were content analysed. Majority of the respondents (78.9%) submitted that although Nigeria has domesticated various gender sensitive policies, there is still a disconnect between policies and actual attainment of gender equality. Reasons for this included lack of unity and commitment among women towards anti-marginalisation practices (60.2%); women preference for men in politics and governance (68.4%); women not showing enough interest and low level participation of women in politics (60.2%). While majority (60.0%) of the respondents agreed that there are existing frameworks for women empowerment, others (67.6%) did not consider these as effective. There were significant relationships between the existing frameworks for women empowerment (p<.05) and women political empowerment, the effectiveness of the frameworks (p<.05), paradigm shift in women’s attitude and perception towards inequality (p<.05). The role of the government was also found significant in women marginalisation (p<.05). Significant relationships existed between unity and oneness among women, women not exploiting opportunities, and women marginalisation in Nigeria (p<.05). The relatively low increase of women in governance during the period under study was agreed by both gender to be caused by women not voting for themselves in party primaries, not supporting selves in party leadership positions, preference for men in power positions, and intra gender wrangling. The FGD participants also agreed that relatively low aspirations in politics among women is a major factor hindering gender parity and gender mainstreaming in governance in Nigeria. Gender inequality in governance has been sustained by attitude and behaviour of women. Women and stakeholders should focus efforts on intra-gender solidarity with current emphasis on affirmative action to achieve accelerated gender parity in governance in Nigeria.